Subjective Well-Being Pada Penderita Kanker Tulang - Restuti, Ranti, Dr. Nanik Prihartanti, M.Si, Psi (2016)
Subjective well-being is an individual evaluation of the quality of life conducted through cognitive evaluation (satisfaction and outlook on life) and affective evaluation (presence of positive emotions and negative emotions felt a little bit). Criteria Informants in this study is a Male / female cancer patients bone, minimum education SMA / SMK / equivalent, is being treated / outpatient in hospitals Moewardi Surakarta, undiagnosed diseases / absence of complications, willing to become informants and smoothly communicate This study uses a qualitative approach to data collection techniques interviews and observation. Results from this study of cognitive evaluation of bone cancer patients have less satisfaction with life because of the influence of the diagnosis of the disease. On the other hand, bone cancer able to think positively and consider the disease as the trials and processes of life should be lived. Bone cancer patients do not consider the disease as a problem, but the impact of the diagnosis that he suffered bone cancer affects the lives of people. However, patients with bone cancer are able to accept and deal with mid troubles, sincere and trusted. From the affective component of bone cancer have a noble hope that wants the accomplishment, which wants to recover, successful and happy family. Feelings felt in the form of bone cancer that positive affect is a sense of fun and happy, and negative affect is felt sadness, anxiety, fear and despair. Other findings in this study are patients with bone cancer have high optimism to get rid of.